Restoration of neutron radiography images - Norehan Mohd. Nor, 1985-; Wan Muhamad Saridan Wan Hassan, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010